Lichen flora in Chandra sal forest: Occurrence, distribution and abundance (Bangladesh Journal of Botany, 2008)
Occurrence of lichen flora in Chandra Sal Forest of Gazipur district, Bangladesh revealed 12 taxa under 2 genera of lichens. These are Anaptychia sp., Anthracothecium variolosum, Bacidia luteola, Chiodecton philippinum, Dimelaena sp., Graphis scripta, Lecanora rugosa, Leptogium sp., Parmelia conspersa, Pertusaria sp., Rhizocarpon sp. and Tylophoron moderatum.The taxa were identified from four different locations of Chandra Sal forest. Symbiotic relationship between algae and fungi revealed that a total of five algal genera namely, Anabaena sp., Gloeocapsa sp., Nostoc sp., Protococcus sp. and Trentepohlia sp. were found to form the thalli of lichens individually with ascomycetous fungi. Nostoc sp. and Protococcus sp. each was found separetely in four lichens. Â  Key words: Lichen, Occurrence, Distribution, Abundance, Sal forest doi:10.3329/bjb.v37i1.1565 Bangladesh J. Bot. 37(1): 61-65, 2008 (June)